UTILIZATION OF GENCIL MOBILE APPLICATION IN IMPLEMENTING SMART CITY IN PONTIANAK - Hidana Nur Jannah (International Journal of Science and Engineering, 2019)
Gencil is a mobile application developed in Pontianak to support the implementation of smart city. The aims of this study are; 1)describing the Gencil mobile application, 2)identifying the utilization of Gencil mobile application, 3)identifying the constraining factors in the development of Gencil mobile application in Pontianak. Primary data was obtained through in-depth interviews and questionnaires. The results show that Gencil mobile application consists of six features. The food price feature becomes the most popular one. Constraining factors for the development of Gencil mobile application are the lack of community participation and the inadequate infrastructure for the application’s development